First‐in‐human randomized study of bimekizumab, a humanized monoclonal antibody and selective dual inhibitor of IL‐17A and IL‐17F, in mild psoriasis. (10th January 2017) - Glatt, Sophie; Helmer, Eric; Haier, Birgit; Strimenopoulou, Foteini; Price, Graham; Vajjah, Pavan; Harari, Olivier A.; Lambert, John; Shaw, Stevan
Abstract : Aims: To assess safety, pharmacokinetics (PK) and clinical efficacy of bimekizumab (formerly UCB4940), a novel humanized monoclonal antibody and dual inhibitor of interleukin (IL)‐17A and IL‐17F, in subjects with mild plaque psoriasis. Methods: Randomized, double‐blind, first‐in‐human study of bimekizumab in 39 subjects who received single‐dose intravenous bimekizumab (8–640 mg) or placebo (NCT02529956). Results: Bimekizumab demonstrated dose‐proportional linear PK and was tolerated across the dose range assessed. No subject discontinued due to treatment‐emergent adverse events and no severe adverse events were reported. Bimekizumab demonstrated fast onset of clinically‐meaningful effects on skin of patients with mild psoriasis as early as Week 2. Maximal improvements (100% or near 100% reductions from baseline) in all measures of disease activity were observed between Weeks 8–12 in subjects receiving 160–640 mg bimekizumab. The duration of effect at doses ≥160 mg was evident up to Weeks 12–20 after a single intravenous dose, dependent on endpoint. Conclusions: This is the first study to demonstrate the safety, tolerability and clinical efficacy of a dual IL‐17A and IL‐17F inhibitor, in subjects with mild psoriasis. Bimekizumab showed fast onset of clinically‐meaningful efficacy by Week 2, with a maximal or near‐maximal magnitude of response that was maintained up to study Weeks 12–20. These findings support the continued clinical development of bimekizumab for diseases mediated by both IL‐17A and IL‐17F, including psoriasis.